Epidemiology and patterns of trauma deaths in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan - Hussain, Hardawani Mohd (2011)
Trauma is an ever increasing problem and it is the leading cause of morbidity and mortality in the under 40s age group in most developed and developing countries including Malaysia. The lack of research into trauma epidemiology is well known. The paucity of information has led to conclusion that proper epidemiological studies cannot be conducted in the absence of meaningful data. The objective of this study is to examine patterns of anatomical injury in victims of trauma death and to determine the probability of survival of trauma death patients. This was a retrospective evaluation of 75 consecutive of trauma files at Hospital Universiti Sains Malaysia, of all trauma death during I year period, beginning I st January 2008 until 31st December 2008. Patients who fulfill the inclusion criteria were selected for the study. Patients were analyzed for injury severity by standard scoring systems (Abbreviated Injury Scale [AIS], Revised Trauma Score [RTS], and Injury Severity Score [ISS], and Trauma and Injury Severity Scale [TRISS] methodology. 75 patients were enrolled. 84% (n=63) were male and 16% (n=l2) were female and all are Malays. Mean age group was 43.0 (SD=27.0). 45 (60%) patients were younger than 55 years old. Blunt injuries 73(97.33%) were the dominant mechanism in fatal trauma whereas penetrating injuries were only 2(2.67%). Majority of trauma death was due to MV A 82.67% (n=62). Total numbers with normotensive SBP (2: 90mmHg) versus hypotensive {<90 mmHg) on arrival were 73 and 2 patients, respectively. For normal respiration (RR 10-29/min) versus respiratory distress (RR>29 /min or <l O/min); the numbers found to be 72 and 3 patients respectively. Noted 18 patient with no or only minor and moderate head injury (GCS2:9) versus 57 patients with severe head injury (GCS<9). Cross-tabulated for age, victims {<55 years) were had a deranged cerebral status (GCS~8; X2-test, df= I, p<0.05) on arrival compare to older victims. The predominant cause of death was CNS injury in 77.3% (n=58), followed by SIRS/MOF in 18.7% (n=l4), exsanguinations 2.7 %( n=2) and others 1.3 %( n= I). Median of ISS was 25 (range: 9-54). The overall mean ISS score was 27 .6±8.6. There was statistically significant difference in the RTS for the three time to death groups (acute:< 48hrs; early: 3-7days; late >7 days) (F=9.820, p < 0.05). When using the Trunkey classification of immediate, early and late deaths, we found that a trend of deaths, clustering in a bimodal-like fashion when stratified according to cause of death. By using TRISS methodology, 62 (82.7%) patient had a Ps >0.5 and 41 of them were judged "frankly preventable" cPs>0.75). Despite a probability of survival above 80%, the early management has thrown up possibilities for prevention of trauma death, improving treatment strategies and enhancing trauma research. Focus on injury prevention is imperative, particularly for brain injuries. The figures from this study, mandate further exploration of preventability issues, management improvements, and areas of clinical awareness that should be apply not only to this trauma system, but also to similar systems as general.